THE CONSTRUCTION CIVIL RESISTANCE UPON PERCEIVED UNSUSTAINABLE INFRASTRUCTURE IN EDWARD ABBEY'S THE MONKEY WRENCH GANG: DISCOURSE ANALYSIS - Putra, Muhammad Andika; Tirmidi , Tirmidi (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study aims to identify central themes and analyze the construction of civil conflict in the novel The Monkey Wrench Gang. The novel depicts civil conflict as a form of resistance against infrastructure development, which is built through environmental degradation, political oppression, and moral dilemmas of resistance. To explore this, this study applies a discourse analysis framework supported by Julia Kristeva's concepts of suprasegmental and intertextuality. The suprasegmental aspect is analyzed through Jan Renkema's psycholinguistic approach, integrating Mandler and Johnson's story grammar theory to analyze narrative structure. Intertextuality is explored to reveal how the novel's discourse connects to broader socio-political and ecological realities, through the lens of James Paul Gee's discourse, language, identity, and the social dynamics of the characters are critically analyzed to reveal that civil resistance is not only a political or environmental act, but also a moral struggle—where characters must choose between personal ethics and destructive resistance. This research contributes to education by encouraging critical engagement with literature to understand ecological resistance, civic responsibility, and moral complexity. It provides insights into how fiction can shape environmental awareness and challenges learners to reflect on justice, activism, and human impact through discourse.